2010
DOI: 10.1002/smll.201001193
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Two‐Dimensional Graphene Nanoconstriction Arrays

Abstract: The fabrication and characterization of two-dimensional nanoconstriction arrays consisting of sub-20-nm graphene constrictions and interconnecting graphene islands are reported. The arrays are fabricated in a scalable top-down fashion using self-assembled close-packed polystyrene nanospheres as lithographic templates and characterized using electron microscopy, Raman spectroscopy, and charge transport measurements. At room temperature, the arrays behave as semiconductors with a field-effect conductance modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 32 publications
4
43
1
Order By: Relevance
“…These oxygen-carbon configurations are the simplest form of ether molecules, but in this case, incorporated within the graphene matrix. One can anticipate that the regular arrays of these highly stable crown ether configurations in graphene can be produced by first forming holes using electrons, ions or chemical reactions [38][39][40][41] and then incorporating oxygen (or nitrogen or sulfur) at the hole edges.…”
Section: Discussionmentioning
confidence: 99%
“…These oxygen-carbon configurations are the simplest form of ether molecules, but in this case, incorporated within the graphene matrix. One can anticipate that the regular arrays of these highly stable crown ether configurations in graphene can be produced by first forming holes using electrons, ions or chemical reactions [38][39][40][41] and then incorporating oxygen (or nitrogen or sulfur) at the hole edges.…”
Section: Discussionmentioning
confidence: 99%
“…On average, the top down etched samples have 1.5x and 2x larger D and D′ Raman defect ratios, respectively, than the more pristine BGCVD samples. Furthermore, the BGCVD materials are also sub stantially better than topdown samples from literature as well, [12,28,29] which have 510x higher Dband Raman defect ratios (see Supporting Information, Figure S7). We hypoth esize that the more substantial defect bands in the topdown samples arise from increased edge roughness (e.g.…”
Section: Communicationmentioning
confidence: 90%
“…To explore the resolution limits of the BGCVD method, we have fabricated graphene nanoribbons ( Figure 2h) and nano perforated graphene (also semiconducting [11,12] ) using electron beam and block copolymer (BCP) lithography, respectively, to create nanopatterned aluminum oxide barrier templates on Cu (Figure 3b). For the latter, we adopted BCP lithography to create a hexagonal array of 16 nm aluminum oxide dots with a periodicity of 41 nm (Figure 3a) on Cu.…”
Section: Doi: 101002/adma201104195mentioning
confidence: 99%
“…[21][22][23][24] GNM, a network of percolating graphene nanoribbons with an ordered pattern, is proposed and fabricated as an effort to overcome such difficulties of graphene nanoribbons by opening up band-gap in a large sheet of patterned graphene as a semiconducting thin film. [25][26][27][28][29][30] It has been demonstrated that GNM can be applied as gas sensors with a high sensitivity. 31 Enthusiasm for GNM-based devices aside, existing research on GNM mainly focuses on its electronic properties, while little study, if not none, has been reported on its mechanical properties, which are crucial for integrating GNM into flexible and stretchable electronic devices or interfacing with other materials.…”
mentioning
confidence: 99%